Juventude Negra, educação e exclusão: um estudo sobre o racismo cotidiano - Costa, Camila Aparecida Oliveira da (2022)
The objective of this research was to investigate if racism is a vector for the exclusion of black young people in the school environment nowadays. The research has a qualitative character and it was developed with eleven students from a public school in the state of Minas Gerais. The methodology of this study used oral testimonies of biographic nature, collected through semi-structured scripted interviews that took place in the students’ houses during COVID-19 pandemic. Therefore, I also aimed to investigate how they see themselves inside the school, in the success or failure of their educational background and what are their perspectives for the future. An important criterion of this research was to choose black students in high school, once they have been in school for longer and considering how important their experiences, interactions and communication are in the construction of representations in that space. That way, they can become aware of the daily racism events that happened through their school lives. Talking and listening to them made it possible for me to think about their testimonies, their complaint about structural racism lived in the foundation of brazilian society that reflects in education, as a consequence of the cultural legacy devaluation, racist slurs directed to their hair and bodies, early school leaving, learning process, the quick entry into the job market, the vicious circle that makes poor people’s dreams become impossible and the social experiences going to waste for being black. In conclusion, the paths this category goes are considered paths of exclusion marked by racism, racial, social and cultural discrimination. They are excluded for being black, for being young, an ignored and stigmatized category, and for being poor.